(untitled) (Brazilian Journal of Radiation Sciences (BJRS), 2024)
Interventional Radiology (IR) plays a major role in neurology. It has several advantages, such as avoiding higher risk surgeries and reducing hospital stay. IR allows the diagnosis of various diseases, such as strokes, neurological dysfunctions, arteriovenous malformations, etc. Despite its advantages, IR delivers high radiation doses to patients, mainly due to long exposure times and the large number of images acquired (cine or DSA mode). In this work, a retrospective study was carried out using information from cerebral arteriography procedures (CAP) recorded in the IRaD (Interventional Radiology Database). Data were extracted from 39 procedures to analyze the frequency of the C-arm X-ray machine projections performed during the procedures and the contribution of the different projections of the C-arm to air kerma and air kerma/image parameters in DSA mode, and this has been done at various angles and for the most commonly used filters. The mean values and standard deviations of total air kerma area product (PKA) and air kerma at the patient entrance reference point (Ka,r) were (7584 ± 4661) µGy·m2 and (746 ± 378) mGy, respectively. It was verified that the total dose delivered to the patient is mainly composed of the dose due to the exposure in DSA mode. In the different C-arm projections during DSA, it was found that the greater the angle of the C-arm (more horizontal), the smaller the air kerma/image value. Also, the more cranial the projection, the greater the air kerma/image value. In the most frequent projections, the equipment was programmed to deliver the lowest doses to the patient by inserting additional copper and aluminum filters.